1989
DOI: 10.1007/bf00305823
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of embryogenic carrot cell cultures and its variations as caused by mutation, differentiation, hormones and hypomethylating drugs

Abstract: The level of auxin - both natural and synthetic - in the medium has a strong effect on the level of 5-methyl-cytosine in the DNA of carrot cells in culture. This level may vary from approximately 15% to 70% of total cytosine without apparent effects on growth rate and cell morphology. No effect was seen with cytokinin. During somatic embryogenesis, in the absence of hormones, variations were seen in the level of methylation according to a characteristic pattern. If hypomethylation is induced with drugs such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(151 citation statements)
references
References 11 publications
8
136
0
6
Order By: Relevance
“…According to Zoglauer (2003), during the induction phase, cells cease their program of specialization and start a new developmental program. The specialization program is negatively affected by the methylation of DNA for which the auxins may play a fundamental role (Lo Schiavo et al, 1989). The carbon source and plant growth regulators supplemented to the culture medium significantly affected the embryogenic induction rate.…”
Section: Resultsmentioning
confidence: 99%
“…According to Zoglauer (2003), during the induction phase, cells cease their program of specialization and start a new developmental program. The specialization program is negatively affected by the methylation of DNA for which the auxins may play a fundamental role (Lo Schiavo et al, 1989). The carbon source and plant growth regulators supplemented to the culture medium significantly affected the embryogenic induction rate.…”
Section: Resultsmentioning
confidence: 99%
“…Also, less differentiated cells contain a lower degree of methylation than fully differentiated mature leaf (Mathieu et al, 2003). It is not certain whether cells with highly methylated DNA are favored for regeneration and selected or whether hormonal factors (LoSchiavo et al, 1989) associated with the regeneration process increase overall genomic methylation.…”
Section: High Interindividual and Low Intraindividual Epigenetic Varimentioning
confidence: 99%
“…The LEC1 gene of Arabidopsis thaliana encodes a protein related to the Heme-Activated Proteins 3 (HAP3) subunit of the CCAAT box-Binding F LRR-RLKs actor (CBF) [102,110]. Kwong et al [101] identified genes encoding Arabidopsis HAP3 subunits in Phaseolus coccineus.…”
Section: Lec Genesmentioning
confidence: 99%